Evolution's empress : Darwinian perspectives on the nature of women - Fisher, Maryanne; Garcia, Justin R., 1985-; Chang, Rosemarie Sokol (Oxford University Press, 2013)
'Evolution's Empress' identifies women as active agents within the evolutionary process. Chapters focus on topics as diverse as female social interactions, mate competition and mating strategies, motherhood, women's health, sex differences in communication and motivation, sex discrimination, and women in literature. The volume editors bring together a diverse range of perspectives to demonstrate ways in which evolutionary approaches to human behaviour have thus far been too limited.